An optimum combination of filament material and slicing software in improving the manufacturing performance of 3D-printed parts / Normariah Che Maideen ... [et al.] - Che Maideen, Normariah; Koay, Mei Hyie; Abdullah, Nor Suhada; Mohd Fohimi, Nor Azirah; Yusoff, Hamid; Mohamad Nahar, Aiman Hakim; Sahudin, Shuib (Penerbit UiTM (UiTM Press), 2025)
Additive manufacturing, or 3D printing, creating a layer of material to produce three-dimensional objects from computer models. Specifically for Fused Filament Fabrication (FFF) that uses filament material, different filament material varies in strength, flexibility, temperature resistance, etc. These factors impact 3D-printed part performance. Apart from filament material, various slicing software that available in the market also influence the manufacturing performance of 3D print parts. Therefore, selecting a correct filament material with suitable slicing software is important. Up to date, the relation between filament materials and slicing software on printed part quality and manufacturing performance is still unknown. Thus, it is necessary to study the manufacturing characteristics of 3D printed parts using different filament materials and slicing software to find the best combinations and parameters for reliable and efficient production of high-quality parts for various applications.